Microbiota and Cardiovascular Diseases: Mechanisms of Influence and Correction Possibilities - A. V. Gorbenko; Y. P. Skirdenko; K. A. Andreev; M. M. Fedorin; N. A. Nikolaev; M. A. Livzan (Рациональная фармакотерапия в кардиологии)
The term "microbiota"  refers to the microbial  community  occupying a specific  habitat  with  defined  physical  and  chemical  properties  and  forming specific  ecological  niches.  The adult  intestinal  microbiota  is diverse.  It mainly  consists  of bacteria  of Bacteroidetes  and  Firmicutes  types.  The link between the gut microbiota  and cardiovascular disease (CVD) is being actively discussed.  Rapid progress  in this field is explained  by the development of new generation  sequencing methods and the use of sterile gut mice in experiments.  More and more data are being published about the influence of microbiota  on the development  and course of hypertension, coronary  heart disease (IHD), myocardial  hypertrophy, chronic heart failure (CHF) and atrial fibrillation (AF). Diet therapy,  antibacterial drugs,  pro- and prebiotics are successfully  used as tools to correct the structure of the gut microbiota of the macroorganism. Correction  of gut microbiota  in an experiment  on rats with coronary  occlusion  demonstrates  a significant  reduction in necrotic area. A study  involving  patients  suffering  from  CHF  reveals a significant  reduction  in the level of uric acid,  highly  sensitive C-reactive protein,  and creatinine. In addition to structural and laboratory changes  in patients with CVD when modifying the microbiota  of the gut, also revealed the effect on the course of arterial hypertension. Correction  of gut microbiota  has a beneficial  effect on the course of AF. We assume  that further active study of issues of influence and interaction of gut microbiota  and macroorganism may in the foreseeable future make significant  adjustments  in approaches to treatment of such patients.